BENTUK KOMUNIKASI ORGANISASI DI JURUSAN KOMUNIKASI DAN PENYIARAN ISLAM UIN AR-RANIRY BANDA ACEH - Putra, Heri Rahmatsyah (Universitas Teuku Umar, 2019)
The purpose of this research is to know the organisation of communication of the Management organization Department of Communication and Islamic broadcasting of Da'wah and communication faculty to be a solution in resolving academic problems. The method used is a qualitative method. The data collection techniques used are observations and live events. This research is located in Darussalam precisely in the Department of Communication and IslamicBroadcasting Faculty of Da'wah and communication State Islamic University Ar-Raniry Banda Aceh and the informant in this study amounted to 5 people. Data analysis is performed using qualitative descriptive approach techniques. The results of the authors showed that the form of communication organization conducted by the Department of Communication and Islamic broadcasting State Islamic University Ar Raniry to lecturers in resolving academic problems in general is a form of Communication, although sometimes also ongoing form of communication top down from the department to the lecturers. Communication is sometimes done directly and also using the media. From the results the authors assess that the form of communication of the Organization has been used to see the phenomenon in the field that lecturers have busy outsidethe campus so that it is not always on campus and can communicate Directly with the majors. Keywords: Forms, Communication, Organization